5-4x+9=2x-10

Simple and best practice solution for 5-4x+9=2x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-4x+9=2x-10 equation:


Simplifying
5 + -4x + 9 = 2x + -10

Reorder the terms:
5 + 9 + -4x = 2x + -10

Combine like terms: 5 + 9 = 14
14 + -4x = 2x + -10

Reorder the terms:
14 + -4x = -10 + 2x

Solving
14 + -4x = -10 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
14 + -4x + -2x = -10 + 2x + -2x

Combine like terms: -4x + -2x = -6x
14 + -6x = -10 + 2x + -2x

Combine like terms: 2x + -2x = 0
14 + -6x = -10 + 0
14 + -6x = -10

Add '-14' to each side of the equation.
14 + -14 + -6x = -10 + -14

Combine like terms: 14 + -14 = 0
0 + -6x = -10 + -14
-6x = -10 + -14

Combine like terms: -10 + -14 = -24
-6x = -24

Divide each side by '-6'.
x = 4

Simplifying
x = 4

See similar equations:

| y+5-2y=5y+3+2x | | 5x+6=3x+9 | | 28-4x=7-7x | | 10x-16=9x+2 | | 5(x+4)=3x+29 | | 4(x+2)-2=18 | | y-3.5=-21 | | -5j+78=8j-2 | | 3x-19=5x+2 | | 5-(2u-1)=14-4u | | x*2-2x=0 | | 3x-19=x-2 | | 2.23-3.14x=2x-4.195 | | 2(4x+3)=2 | | 4x-15=x+10 | | 5x-12=2x-9 | | 2H+4S=22 | | 5(x-3)=-13 | | 19-x+4+x+19+x-1=34 | | 3x=1.08 | | F(x)=(radx-2)-3 | | ln(3-7x)=-2 | | 3x+1.66=1.8 | | 10x^3+58x^2+43x-11=0 | | 10x^3+58x^2+43x-11=f(x) | | 24x=-16x^2+6 | | 5x-7y=29 | | 5cos(x)=0 | | 0.04*0.8= | | x+(2x+15)=150 | | 0.75d-0.67d=0.67+6 | | 88+5x= |

Equations solver categories